A New Design Optimization Method For Energy and Indoor Thermal Performance of Apartment Buildings. Issue 4 (1st July 2018) - Yao, Jian
ABSTRACT: To improve the energy and indoor thermal performance of apartment buildings, this =paper developed a new design optimization index ITDH (indoor thermal performance difference between housing units). Five conventional design optimization options were compared with the ITDH-based design option by using building simulation and room base temperature. Energy consumption of different housing units were also calculated. It was found that the new design optimization method performed much better than the conventional method in reducing the differences of the energy and indoor thermal performance between housing units. ITDH is, therefore, an effective and important evaluator for a successful energy design of residential buildings and can be widely used for optimization of current building designs in China.